HIGH PREVALENCE OF OBESITY AND PHYSICAL INACTIVITY AMONG SELECTED WORKERS IN KANO STATE NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
There is increasing burden of cardiometabolic diseases in Africa. Increasing rates of physical inactivity and obesity are partly responsible for this development. The aim of this study was to determine the prevalence of physical inactivity and obesity among selected workers in Kano State, Nigeria. In this cross sectional study of 466 workers attending a part-time degree program at Bayero University Kano, Nigeria, body weight was measured using a standard digital weighing scale, body height was measured using a portable stadiometer, circumferences (waist and hip) were measured using an inelastic measuring tape and physical inactivity using a standardized questionnaire. Data analysis was done in R statistical environment. The subjects consisted of 280 males and 186 females with respective mean ages of 37 (±8.7) and 36 (±9.6). Mean waist circumference for males and females was 87.9 (±13.4) and 86.4 (±13.2) respectively. Both males and females sit on an average of 10 hours per weekday. Almost 2/3 of both male and female subjects were physically inactive. About the same proportion of the study subjects have generalized obesity (58% of male and 66% of female subjects). More than ¾ of female subjects and 2/3 of male subjects were centrally obese using waist-to-hip ratio measure. The high prevalence rates of physical inactivity and obesity among this group of urban workers mean they are at a particularly high risk of cardiometabolic diseases and should be a priority group for public health intervention programs designed to reduce the burden of cardiovascular disease and diabetes.
Keywords: Physical inactivity; Obesity; Cardiovascular disease; Diabetes; Nigeria